Biofilm cultivation facilitates coexistence and adaptive evolution in an industrial bacterial community - Nathalie N. S. E. Henriksen; Mads Frederik Hansen; Heiko T. Kiesewalter; Jakob Russel; Joseph Nesme; Kevin R. Foster; Birte Svensson; Gunnar Øregaard; Jakob Herschend; Mette Burmølle (npj Biofilms and Microbiomes, 2022)
Abstract The majority of ecological, industrial and medical impacts of bacteria result from diverse communities containing multiple species. This diversity presents a significant challenge as co-cultivation of multiple bacterial species frequently leads to species being outcompeted and, with this, the possibility to manipulate, evolve and improve bacterial communities is lost. Ecological theory predicts that a solution to this problem will be to grow species in structured environments, which reduces the likelihood of competitive exclusion. Here, we explored the ability of cultivation in a structured environment to facilitate coexistence, evolution, and adaptation in an industrially important community: Lactococcus lactis and Leuconostoc mesenteroides frequently used as dairy starter cultures. As commonly occurs, passaging of these two species together in a liquid culture model led to the loss of one species in 6 of 20 lineages (30%). By contrast, when we co-cultured the two species as biofilms on beads, a stable coexistence was observed in all lineages studied for over 100 generations. Moreover, we show that the co-culture drove evolution of new high-yield variants, which compared to the ancestor grew more slowly, yielded more cells and had enhanced capability of biofilm formation. Importantly, we also show that these high-yield biofilm strains did not evolve when each species was passaged in monoculture in the biofilm model. Therefore, both co-culture and the biofilm model were conditional for these high-yield strains to evolve. Our study underlines the power of ecological thinking—namely, the importance of structured environments for coexistence—to facilitate cultivation, evolution, and adaptation of industrially important bacterial communities.